1977
DOI: 10.1007/bf00500898
|View full text |Cite
|
Sign up to set email alerts
|

Increased level of cAMP in the rat intestinal musosa caused by sodium lauryl sulphate

Abstract: The level of cyclic AMP in the jejunal mucosa from tied loops of anaesthetized rats was found to be significantly increased (27-50%) when sodium lauryl sulphate (SLS) was added to the loop fluid (2-27 mM). Imidazole (25 mM) did not significantly alter the resting level of cyclic AMP, but reduced the increase caused by SLS (17 mM). Theophylline (25 mM) significantly increased the intestinal level of cyclic AMP, and potentiated the increase caused by SLS. Ouabain (2.5 mM) did not alter the level of cyclic AMP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the present work, these two possibilities have been explored by studying the influence of theophylline and DOSS on the abovementioned absorption processes in vivo. Another anionic surfactant, dodecylsulphate (=DDS), was also included, since this drug may induce some increased formation of CAMP (Briseid et al 1976(Briseid et al & 1977Sund & Hillestad 1981). A short account of this study has been presented elsewhere (Sund & Olsen 1978).…”
mentioning
confidence: 99%
“…In the present work, these two possibilities have been explored by studying the influence of theophylline and DOSS on the abovementioned absorption processes in vivo. Another anionic surfactant, dodecylsulphate (=DDS), was also included, since this drug may induce some increased formation of CAMP (Briseid et al 1976(Briseid et al & 1977Sund & Hillestad 1981). A short account of this study has been presented elsewhere (Sund & Olsen 1978).…”
mentioning
confidence: 99%
“…In the present work, these two possibilities have been explored by studying the influence of theophylline and DOSS on the abovementioned absorption processes in vivo. Another anionic surfactant, dodecylsulphate (=DDS), was also included, since this drug may induce some increased formation of CAMP (Briseid et al 1976(Briseid et al & 1977Sund & Hillestad 1981). A short account of this study has been presented elsewhere (Sund & Olsen 1978).…”
Section: Key-wordsmentioning
confidence: 99%
“…During the last decade it has been shown that the potent hydragogue toxin from Vibrio cholera causes stimulation of the mucosal adenylate cyclase/cAMP system; this in turn leads t o luminal water and electrolyte accumulation probably by stimulation of cellular anion efflux or inhibition of coupled sodium-anion influx. The question has been raised if also hydragogue drugs may act o n this system, and research along this line has been stimulated Briseid et al 1976Briseid et al & 1977Conley et al 1976a & b;Coyne et al 1976Coyne et al & 1977Donowitz & Binder 1975;Gaginella et ai. 1978;Loeschke 1979;Simon et al 1978;S i m o n & Kather 1980;S u n d & Hillestad 1978), with different results a s t o the significance of t h e system f o r t h e hydragogue effects.…”
mentioning
confidence: 99%